Identifikasi Titik Kritis Kehalalan Bahan Nabati Dan Produk Turunan Bahan Nabati - Jumiono, Aji; Mardiah, Mardiah; Amalia, Lia; Puspasari, Erna (Universitas Djuanda, 2023)
Materials derived from plants (vegetable) are basically halal because there is no shari'a argument which specifically mentions the prohibition of the types of materials derived from plants, but if they have been processed using additives or processing aids that are not halal then the status of the product may become non-halal. . This paper uses a review of literature from various main references in the criteria for halal certification and knowledge of materials and processing of plant-based products. Identification of critical points for vegetable ingredients can be analyzed using a decision tree for identifying critical points for halal vegetable ingredients. Products derived from vegetable materials can be contaminated with unclean/unclean materials if there are additional ingredients and processing. The various processed plant food products in this article are complemented by the results of a study identifying their critical points starting from dried plant materials, wheat flour to starch and its derivatives. Vegetable ingredients are doubtful and their halal status needs to be criticized if they have undergone processing and the use of additional ingredients.